Efecto de factores ambientales en la persistencia de la producción láctea de vacas brown swiss, en Ecuador - Mina Vega, Verónica Cristina (2023)
The research was carried out in the provinces: Chimborazo, Imbabura, Carchi, Napo, Pichincha, Tungurahua and Cotopaxi in Ecuador. The objective of the study was to determine the effect of environmental factors on the persistence of lactation in Brown Swiss cows. Milk production was calculated using the Fleischmann methodology and persistence according to the Johanson and Hansonn procedure. The data were analyzed in a general linear model_ GLM in the SAS, v.w. 9.4. In the comparison of the least square means, the Tukey Kramer test was used. Descriptive statistics of the variable’s persistence (PER_JH), lactation duration (DLAC), total milk (LTOTAL), milk adjusted to 305 days (L305), milk per day (LDIA) were calculated. The environmental effects studied were year of delivery (YEAR_P), month of delivery (MONTH_P) and semester of delivery (SEM_P). The parameters of PER_JH were determined at 0.7162 ±0.01; LTOTAL, 4911.98 ±76.34 kg; LAJUST, 5095.46 ±80.14 kg; LDIA at 16.98 ±0.27 kg. DLAC, 9.05 ±0.02 months. The PER_JH was not affected by the environment (P>0.05). The correlations between the LTOTAL and LDIA, L305 were 0.9751 (P<0.001), for the PER_JH and the variables of interest were not significant (P>0.05). It is concluded that the environmental effects AÑO_P, MES_P and SEM_P, did not have a manifestation in the PER_JH under the breeding systems and environmental conditions in Ecuador.